COVID-19 and Pulmonary Tuberculosis Coinfection in a Moroccan Patient with Pulmonary Embolism: A Case Report and Literature Review - Imane Zouaki; Zakaria Chahbi; Mohamed Raiteb; Mohamed Zyani (Case Reports in Infectious Diseases)
Emerging cases of coinfection of coronavirus disease 2019 (COVID-19) and tuberculosis (TB), although rare, have attracted the attention of health systems around the world and have arisen many concerns about the diagnosis, treatment, and prognosis of this coinfection especially in high TB burden countries. Here, we report a rare case and, to the best of our knowledge, the first reported case in Morocco of simultaneous diagnosis of an active pulmonary TB infection and a COVID-19 pneumonia. We present a case of a sixty-seven-year-old male patient who was admitted to our COVID-19 emergency department with a diagnosis of COVID-19 pneumonia, confirmed by nasopharyngeal swab’s polymerase chain reaction (PCR) for detection of SARS-CoV-2. The atypical radiological findings suggested a TB coinfection which was later confirmed by sputum cultures and Xpert MTB/Rif assay. The patient also presented some complications including thrombosis of the left leg, pulmonary embolism and inaugural ketosis. Treatment was administered as per local protocols: broad spectrum antibiotics, corticosteroids, fixed dose-combination of antituberculosis treatment along with hydration and insulin therapy for ketosis treatment and anticoagulation. The patient was discharged after twenty-three days of hospitalization. Due to the currently limited data, further studies are necessary to establish any possible correlation between COVID-19 infection and the progression of a latent and/or the severity of an active TB infection.